Causes of the occurence of malting barley kernel discoloration - Petr, Jiří; Capouchová, Ivana (BrewingScience, 2001)
The blackened tips of barley grains disclose a certain flaw and they can bring a risk of a negative effect on the quality of malt and beer. The decisive effect on the occurrence of blackened tips of malting barley had rainy weather at the time of caryopsis formation and maturation, i.e. 20 days after earing till harvesting. The highest effect was found within the period of 30–40 days after earing of barley. One-shot, even high precipitations are not so dangerous as smaller amounts of precipitations, but frequent for a longer period of time. The factor of weather at the time period indicated to be as decisive and predominated over the effects of other ecological and growing factors. The data on precipitation course and relative humidity 15 to 40 days before harvesting could serve as a possible forecast of the occurrence of blackened tips of malting barley grains. The varietal susceptibility of malting barley varieties to the blackened tips of barley grains was found. This varietal susceptibility should be monitored during the new varieties of spring malting barley breeding and evaluation. The effect of some other factors influencing the occurrence of this kind of damage can be interpreted as reflection of plant stress. These factors can be a low pH value of soil (the effect of soil acidity), aluminium ions content and the effect of heavy soils. The similar effect had the damage of plant nutrition, e.g. a high content of nitrogen in soil or high fertilizing by nitrogen and potassium. On the other hand, the effect of phosphorus, magnesium and some microelements (Cu, Mo, Zn) was positive. The presence of pathogens, but in interaction with bad weather course at the time of caryopsis formation and maturation, is considered to be the main cause of the biological damage of barley grains. Health condition of vegetation also contributes to the damage of barley grains, when the attack of vegetation by powdery mildew (Blumeria graminis), net blotch (Helmithosporium teres) and scald (Rhynchosporium secalis) likely caused the enfeeblement of the plants and the percentage increase of damaged grains. For monitored vegetation pickled seeds were used and the vegetation was at least once treated against diseases, but also this procedure did not protect the vegetation from the occurrence of blackened tips. Also individual trials of treatment by means of various types of fungicides did not show demonstrably positive results. However, the blackened tips of barley grains do not have to be in all ways the carriers of fungal and bacterial pathogens causing so-called gushing – beer foaming over.